Reviews of recent publications (Studies in 20th & 21st Century Literature, 1994)
Paisley Livingston. Models of Desire: René Girard and the Psychology of Mimesis by Andrew J. McKenna Andrew J. McKenna. Violence and Difference: Girard, Derrida, and Deconstruction by Servanne Woodward James F. Murphy. The Proletarian Moment: The Controversy over Leftism in Literature by Jack Marmorstein Chris Bongie. Exotic Memories: Literature, Colonialism, and the Fin de Siecle by Annelise Riles Luce Irigaray. Marine Lover of Friedrich Nietzsche. Trans. Gillian C. Gill by Marianne Bosshard Christie McDonald. The Proustian Fabric: Associations of Memory by Rebecca Karoff Kathryn Hume. Calvino 's Fictions. Cogito and Cosmos by Gian-Paolo Biasin Peter Baker. Obdurate Brilliance: Exteriority and the Modern Long Poem by Steven Winspur
Keywords: Paisley Livingston; Models of Desire: René Girard and the Psychology of Mimesis; Andrew J. McKenna; Violence and Difference: Girard; Derrida; and Deconstruction; James F. Murphy; The Proletarian Moment: The Controversy over Leftism in Literature; Chris Bongie; Exotic Memories: Literature; Colonialism; and the Fin de Siecle; Luce Irigaray; Marine Lover of Friedrich Nietzsche. Trans. Gillian C. Gill; Christie McDonald; The Proustian Fabric: Associations of Memory; Kathryn Hume; Calvino& #x27; s Fictions. Cogito and Cosmos; Peter Baker; Obdurate Brilliance: Exteriority and the Modern Long Poem; Jack Marmorstein; Annelise Riles; Marianne Bosshard; Rebecca Karoff; Servanne Woodward; Gian-Paolo Biasin; Steven Winspur